In Search of a Boundless Ocean and New Skies: Human Creativity is a Matter of A‘mal, Jihad, and Ijtihad (American Journal of Islam and Society, 1996)
The stars tremble in their courses over man’s upward march lestthis fallen star should become the perfect moon!’The central question this article addresses is whether human beingscan act creatively. I shall first tackle the related question of how God’s creativityis distinguished from that of humanity and then move on to themore complex question of the nature of human creativity.God’s Creativity is Different from That ofHumankindThe Qur’an relates rubb (lord) to khalq (creation):He said: “Our Lord [rubb] is He who gives to everythmg its . . .[khalq] . . . and further gave (it) guidance. (Qur’an 20:50)’The noun khalq is considered by lexicographers to be derived from theroot verb khaluqu (to create, to make, to originate). And if God (ulKhaliq) created or orignated, then khalaqa is a verb that signifies His creativeability. According to al Raghib, khalq is used to describe the creativity(ibda) of a thing without imitation (ikhtiza’): He assigns this roleof khulq to God (al Khaliq). For a1 Tabataba‘i “the God of the universe isone, He alone created and He alone manages it.“ In fact, the link betweenGod as rabb and khalq is accentuated by al Tabari, who considers rubb tobe “the owner to whom the creation . . . belongs.’“ Moreover, this...